2018
DOI: 10.31235/osf.io/96umt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When populists become popular: Comparing Facebook use by the right-wing movement Pegida and German political parties

Abstract: Previous research has acknowledged the use of social media in political communication by right-wing populist parties and politicians. Less is known, however, about its pivotal role for right-wing social movements which rely on personalized messages to mobilize supporters and challenge the mainstream party system. This paper analyzes online political communication by the right-wing populist movement Pegida and German political parties. We investigate to which extent parties attract supporters of Pegida, to whic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 14 publications
2
38
0
4
Order By: Relevance
“…In a second step, we will investigate whether the characteristics of communication channels and the properties of parties affect the degree of populist communication on social media and political talk shows. Recent research has demonstrated the importance of Facebook and Twitter for populist communication (e.g., Bracciale & Martella, 2017;Hameleers & Schmuck, 2017;Stier, Posch, Bleier, & Strohmaier, 2017). However, these studies lack a comparison of different media channels.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…In a second step, we will investigate whether the characteristics of communication channels and the properties of parties affect the degree of populist communication on social media and political talk shows. Recent research has demonstrated the importance of Facebook and Twitter for populist communication (e.g., Bracciale & Martella, 2017;Hameleers & Schmuck, 2017;Stier, Posch, Bleier, & Strohmaier, 2017). However, these studies lack a comparison of different media channels.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…In early 2018, in the aftermath of the Cambridge Analytica (CA) scandal, Facebook drastically tightened the access to its Application Programming Interface (API). For almost 10 years, the API served as the main tool by which researchers collected behavioral and digital trace data from Facebook (for some recent examples, see Abdulla et al, 2018;Braun & Schwarzbözl, 2018;Larsson, 2016;Poell et al, 2016;Stier et al, 2017). By using the API, independent researchers and third parties were able to easily download public information about users' profiles, as well as comments and reactions to public posts, to study the impact of social media on society.…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that users agree to publish on social media a huge amount of data about their political and non-political preferences and behaviour, these platforms are an ideal source for political knowledge extraction. Social media have become a key environment for political campaigns, as the majority of politicians can use them to communicate directly with the electoral body (Barbera´and Zeitzoff, 2017; Hegelich and Shahrezaye, 2015;Medina Serrano et al, 2019;Nulty et al, 2016;Stier et al, 2017). That aside, political actors often perform organized influencing strategies on social media, frequently trespassing the legal limits set (Weedon et al, 2017).…”
Section: Microtargeting In Theorymentioning
confidence: 99%